1989
DOI: 10.1073/pnas.86.6.2070
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 potentiates the secretion of beta-endorphin induced by secretagogues in a mouse pituitary cell line (AtT-20).

Abstract: Previous work has shown that corticotropin releasing factor, vasoactive intestinal peptide, phorbol ester, and forskolin cause the secretion of adrenocorticotropic hormone and ,3-endorphin from the AtT-20 mouse pituitary cell line. Human recombinant interleukin la and 1(3 also stimulated adrenocorticotropic hormone and (3-endorphin secretion from AtT-20 cells in a time-and dose-related manner. The effect appeared only after pretreatment with interleukin 1 (IL-I) for at least 18 hr and was maximum at 24 hr. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…1). These observations are in contrast to those obtained with TPA and TPA together with IL-1, where desensitization of PKC abolished the secretory effects of TPA as well as the potentiating effect on TPA-elicited secretion induced by pretreatment with IL-1 (1).…”
Section: Methodscontrasting
confidence: 55%
See 1 more Smart Citation
“…1). These observations are in contrast to those obtained with TPA and TPA together with IL-1, where desensitization of PKC abolished the secretory effects of TPA as well as the potentiating effect on TPA-elicited secretion induced by pretreatment with IL-1 (1).…”
Section: Methodscontrasting
confidence: 55%
“…It has been recently demonstrated that human recombinant IL-1, after a long pretreatment (at least 18 hr), stimulates the release of f-endorphin in AtT-20 cells (1). Previous work in our laboratory has shown that prolonged pretreatment with IL-1 also potentiates the secretion induced by secretagogues such as corticotropin-releasing factor (CRF), vasoactive intestinal peptide, forskolin, norepinephrine, isoproterenol, and phorbol ester [phorbol 12- by IL-1 (1).…”
mentioning
confidence: 99%
“…In the presence of permissive levels of CRF, the increased expression of POMC mRNA and increased ACTH secretion is presumably due to the combined effect of high levels of AVP and the presence of locally produced (Stephanou et al, 1993) or circulating cytokines, which are likely to be elevated during chronic inflammation. In this regard it has been shown that prolonged exposure of AT-20 cells or rat cultured pituitary cells to interleukin-1 (IL-1) potentiates fl-endorphin responses to subsequent incubation with CRF (Fagarasan et al, 1989).…”
Section: Avp Receptor Assaymentioning
confidence: 99%
“…Another group was pretreated by first injecting ahCRF earlier observation [84]. Beginning with the original demonstration of IL-1-induced ACTH release from a corticotroph cell line [3], AtT20, and subsequent confirmations and demonstrations of this response with primary pituitary cell cultures [85][86][87][88][89][90], a controversy ensued as to whether in vivo IL-1-mediated ACTH increases originated at the level of the hypothalamus or pituitary gland [91]. Although the consensus of studies concluded that ACTH release occurs as a result of IL-1 eliciting hypothalamic CRH release and that the CRH is entirely responsible for pituitary ACTH secretion [92][93][94][95], these findings were difficult to reconcile with the abundance of IL-1 receptors in the pituitary gland when compared with the hypothalamus [96,97].…”
Section: Future Directions For the Sixth Sensementioning
confidence: 99%